Lung Biology and Pathophysiology (Taylor & Francis, 2024)
asthma; cystic fibrosis; gas exchange; homeostasis; inflammation; lung diseas; lung endothelium;stem cells
English
Keywords: Biology, life sciences; Cellular biology (cytology); Clinical & internal medicine; Immunology; Molecular biology; asthma; cystic fibrosis; gas exchange; homeostasis; inflammation; lung diseas; lung endothelium;stem cells